Attitudes toward elderly workers and perceptions of integrated age management practices. Issue 1 (2nd January 2020) - Blomé, Mikael Widell; Borell, Jonas; Håkansson, Carita; Nilsson, Kerstin
Abstract : This qualitative study investigates attitudes toward elderly workers and their work situation in different sectors, and explores perceptions and organizational measures that can enable an extended working life. Previous age management studies indicate that there are several interconnected measures and key areas of importance, and that there is a general need for strategies to strengthen sustainable age management at the organizational level. A structured content analysis was used to analyze data from focus group interviews with informants from a variety of organizations. The study identified three themes that highlight attitudes and perceptions of integrated age management practices: (a) contemporary policies and practices in the work environment; (b) social participation and attitudes; (c) experience and mentorship. These themes can form the basis of a good approach to an integrated age management strategy. Such a strategy can be achieved through intervention studies where research on sustainable working life meets the real problems faced by employees and managers.